Analisis Semiotika Makna Pesan Foto Terbaik Pada Buku Treasure Of Sukabumi - Anne Sandra Dewi; Nenden Muslihat (KOMVERSAL, 2024)
Photo is one of the visual works that can convey a message in the form of an image without any manipulation or engineering process. Sukabumi is one of the areas in West Java that has amazing tourism potential ranging from natural, culinary, historical, educational, to cultural tourism. Treasure Of Sukabumi is a photo book that tells about the treasures owned by Sukabumi. This study aims to determine the connotation and denotation meanings of the best photos in the book Treasure Of Sukabumi. This study uses a qualitative approach using Roland Barthes’s Semiotic theory method which reads images through denotative meanings and connotative meanings. Data collection techniques using observation techniques, in-depth interviews, documentation and triangulation techniques. There were five informants in this study, with a side purposive technique. The objects of this research are the two best photographs of the book Treasure Of Sukabumi. The results of the study show that there is a denotative meaning in the form of the actual conditions contained in the photos of Goa Buni Ayu and the Cap Go Meh Celebration and connotation meanings based on trick effect (artificial effect), body pose or gesture, object, photogenia (photo technique), aestheticism (composition), and syntax in the photos of Goa Buni Ayu and the Cap Go Meh Celebration so that they contain additional meanings, certain feelings or certain taste values ​​in addition to the general basic meaning. The conclusion of this study is to show the charm of the beauty of underground tourist destinations and the potential wealth of tourism owned by Sukabumi.